Examination of the knowledge gap of return-to-work outcomes in routine outpatient treatment for common mental disorders: a systematic review - Lundqvist, Jakob; Brattmyr, Martin; Lindberg, Martin Schevik; Havnen, Audun; Solem, Stian; Hjemdal, Odin (Frontiers in Psychology, 2023)
Objective. Little is known about the effects of routine mental health care on return-to-work (RTW) outcomes. This systematic review aimed to summarize and evaluate the effects of clinical representative psychotherapy on RTW among patients with a common mental disorder (CMD), treated within public mental health care.Method. A systematic search was conducted using PubMed, PsycINFO, Embase, and SveMED+. Primary outcomes were RTW, sick leave status, or self-reported work functioning. Studies limited to specific treatments and/or specific patient groups were excluded.Results. Out of 1422 records, only one article met the preregistered inclusion criteria. After broadening of criteria, a total of nine studies were included. Six were randomized controlled trials (RCT), two were register-based studies, and one was a quasi-experimental study.Descriptions of treatment duration and intensity of usual care were rarely specified but ranged from a few sessions to 3 years of psychotherapy. In the RCTs, two studies favored the intervention, one favored routine care, and three found no difference between conditions.Choice of outcomes differed greatly and included RTW rates (full or partial), number of days until RTW, change in sick leave status, and net days/months of work absence. Time points for outcome assessment also varied greatly from three months to five years after treatment.There is inconclusive evidence to establish to what extent routine mental healthcare is associated with improved RTW outcomes for patients with CMD. There is a need for more and better clinical trials and naturalistic studies detailing the content of routine treatment and its effect on RTW.